Asistensi The Effect of Quality of Work Life and Teamwork on Employee Performance Moderated Work Effectiveness on CV. Ibnu Aqil Mandiri Lubuk Pakam - Atika Aini Nasution (Jurnal Mantik, 2022)
From the initial research that researchers do, the phenomenon at the office of CV. Ibnu Aqil Mandiri Lubuk Pakam, among others, placement of employees who have not been in accordance with the demands of office and educational background, so as not to meet the capacity capability as appropriate. The need for competent employees in accordance with the position of his position that has not sufficient cause the consequences of less responsible attitude towards his work, the motivation for achievement to be lost, not enthusiastic in work and feeling saturated. Such trends can occur in CV. Ibnu Aqil Mandiri Lubuk Pakam, all of this stems from the mismatch of employee position placement with existing work load so that the interest or job satisfaction of employees decreased, while in terms of facilities and infrastructure and has been very supportive of employees in completing their work. The purpose of this study was to determine the effect of work placement, workload and organizational culture on work motivation at CV. Ibnu Aqil Mandiri Lubuk Pakam. The number of samples in this study amounted to 79 people using saturated sample technique. The analysis technique used is multiple linear regression. The results showed that simultaneously work placement variables, workload and organizational culture have a significant effect on employee work motivation. Job placement has no significant effect on employee work motivation, work load and organizational culture have an effect on employee work motivation